2013
DOI: 10.1155/2013/590730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naked Gold Nanoparticles on Proinflammatory Cytokines mRNA Expression in Rat Liver and Kidney

Abstract: The data on the biocompatibility of naked gold nanoparticles (GNPs) are scarce, and their interpretation is controversial. We studied the acute (1 day) and subchronic (5 days) effects of GNPs (10 and 50 nm diameter) on expression of interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) in the liver and kidneys of rats. In the liver, the GNPs of both sizes (10 and 50 nm) significantly increased the cytokines gene expression on day 1 which was subsided on day 5; the GNPs of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 42 publications
5
51
1
Order By: Relevance
“…IL-2 and IL-6 regulate cell proliferation and cytokine secretion, whereas TNF-α regulates immunity, inflammation, and apoptosis (Bradley, 2008;O'Shea et al, 2008). Other studies have found that AgNPs and AuNPs upregulated cytokine expression in other cell types (Yen et al, 2009;Khan et al, 2013). However, we found that AgNPs inhibit TNF-α in Jurkat cells and AuNPs inhibit IL-2 and IL-6 in Jurkat and U937 cells in a concentration-dependent manner.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…IL-2 and IL-6 regulate cell proliferation and cytokine secretion, whereas TNF-α regulates immunity, inflammation, and apoptosis (Bradley, 2008;O'Shea et al, 2008). Other studies have found that AgNPs and AuNPs upregulated cytokine expression in other cell types (Yen et al, 2009;Khan et al, 2013). However, we found that AgNPs inhibit TNF-α in Jurkat cells and AuNPs inhibit IL-2 and IL-6 in Jurkat and U937 cells in a concentration-dependent manner.…”
Section: Discussioncontrasting
confidence: 80%
“…AgNPs and AuNPs upregulate the expression of the proinflammatory genes interlukin-1 (IL-1), interlukin-6 (IL-6), and tumor necrosis factor (TNF-α) in macrophage cells (Yen et al, 2009). Furthermore, AuNPs have been shown to significantly increase the expression of IL-6 and TNF-α in the kidneys of rats (Khan et al, 2013). Cytokines are signaling molecules that mediate and regulate cellular activities.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al 41 concluded that AuNPs (50 nm) resulted in a normal level of IL-6 gene expression in the hepatic tissue of rats on day 5 postinjection, while IL-1β and TNF-α mRNA expression was downregulated significantly on day 5. Moreover, AuNPs have no cytotoxic effect since they decrease the production of reactive oxygen species and do not stimulate secretion of pro-inflammatory cytokines (TNF-α and IL-1β) making them suitable candidates for nanomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor kappa B (NF-kB) may regulate phagocyte activation via the induction of cytokine production. 13 Khan et al 14 studied the time course of the effects of 10 and 50 nm diameter naked GNPs on the expression of proinflammatory cytokines, including interleukin (IL)-1 beta (IL-1β), IL-6, and tumor necrosis factor alpha (TNF-α), in the liver and kidneys of rats. In the liver, the GNPs of both sizes (10 and 50 nm) significantly increased cytokine gene expression on Day 1, which subsided by Day 5; however, the 50 nm GNPs produced a more severe inflammatory response compared to the 10 nm GNPs.…”
mentioning
confidence: 99%